R.O. Jakobson et N.S. Troubetzkoy : deux personnalités, deux sciences ? - Plungjan, Vladimir A. (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
Vladimir PLUNGJAN, Institute of Linguistics, Moscow : «R. Jakobson and N. Trubetzkoy : two figures, two sciences?» The structuralist Prague school has often been presented as a monolithic whole, as far as the basic theoretical principles are concerned. There are certain attempts to distinguish a «Western» and an «Eastern», or «Russian» structuralism, but the latter remains, for its commentators, a homogeneous phenomenon. This papers, resting upon Trubetzkoy’s and Jakobson's correspondence, asserts that this opinion is justified only to a certain extent. First of all, personal differences are striking. Trubetzkoy's «classical» spirit, his taste (or obsession) for what is «achieved», the coherent «system» of every phenomenon has to be compared to Jakobson 's «Romantic» spirit (Trubetzkoy himself calls it «Bohemian»), which cultivates what is «unachieved» and «fragmentary». Apart from those superficial differences, there are deeper ones, revealing two different scientific personalities. In particular, the following problem is discussed: who is the «real» structuralist? Perhaps neither Jakobson nor Trubetzkoy?